Geopolymers based on plasma incineration waste as a material for circular economy. Issue 1 (November 2021) - Plawecka, K; Figiela, B; Grela, A; Buczkowska, K E
Abstract: Plasma waste treatment technology is one of the promising methods of reducing problematic waste, but the technology itself create other kind of waste that must be effectively used to recognize this technology as a suitable for circular economy. The aim of the article is to show the possibility of using waste materials from a plasma incineration plant as a raw material for the production of geopolymeric materials. The samples were made based on waste from plasma incineration plant in Liberec (Czech Republic), fly ash from thermal power plants in Skawina (Poland) and sand mixed with an aqueous chemical solution. Next they mechanical properties, microstructure and mineralogical composition have been investigated. The results show the combination of these raw materials can increase the strength of the material and, consequently find applications in the utilization of plasma incineration waste. The article show the geopolymerization could be effective process for using waste materials from a plasma incineration plant as a raw material for creating the products for construction industry.